Phenomenological study on the lived experience of millennial moms decision-making process in choosing birthplace - Ismail, Farah Raihana (2022)
The decision of birthplace is one of the most important phases in a woman's life. It has a significant impact on women's psychological development and well-being. In Malaysia, millennial moms significantly contributed to the birth rate. Malaysia’s vital statistics show the average age of the mother at first live birth in Malaysia was among the millennial mom generation. Millennial moms, who contributed to a sizable proportion of childbirth in Malaysia, exhibit distinct characteristics, shifting the demographic landscape, particularly in healthcare service decision-making. The birthplace decision-making process has evolved significantly due to technological advancements. As a digital-savvy generation, millennial moms rely mostly on digital communication platforms (i.e., SNS, Google) in making health-related (birthplace) decisions. In the era of digital evidence-informed healthcare, information is almost instantaneous. The digitalization communication platform has altered consumer decisions, preferences, and behavioral patterns, with millennial moms fixating on other moms' reviews and experiences to make birthplace consumption decisions. The online sharing of experiences and testimonials facilitates millennial moms to make more informed birthplace decisions. The rise of consumer-centric healthcare services saw millennial moms treated as consumers rather than patients, moving away from a paternalistic decision-making approach in choosing their birthplace. However, scarce details are known on the details process of how millennial moms make the birthplace decision. Existing birthplace studies were evaluated from a medical and organizational perspective, omitting the consumer-centric approach as part of the decision-making process. Meanwhile, the prior consumer decision process model (i.e., Engel, Blakewell, and Minniard, EBM) does not consider the proliferation of online sharing, reviews, virtual communication, and non-cognitive aspects as part of the decision process. To address this issue, the main objective of this study is to explore the lived experience of millennial moms' consumer decision-making process in choosing their birthplace. This study employed qualitative descriptive phenomenological research inquiry. The data is collected using in-depth interviews and informal observation (i.e., field notes). Colaizzi’s descriptive phenomenology was applied to analyze the data. A final total of six participants were involved in this study. The number of participants for this study is determined upon reaching the saturation point of the phenomenology inquiry. Participants were selected using maximum variation sampling based on the pre-requisite criteria (i.e., experienced millennial moms, had a positive/negative/both birthplace experience), middle-income earners, gave birth at a government hospital/ private hospital/both government and private hospitals. Findings in this study identified the details decision-making stages where eight major themes emerged; (1) need recognition, (2) information stage, (3) alternative evaluation, (4) pre-decision, (5) decision, (6) postservice evaluation, (7) consumer continuum of involvement, and (8) variables influences decision process. This study yielded three major conclusions. First, the decision stages are not fixed to order, which prior birth experience helps expedite the decision process and reduce the number of decision cycles. Second, the participant's level of involvement in birthplace decision-making varied according to the outcome of the birthplace experience. It has been discovered that the more satisfying the birthplace experience, the lower the level of involvement in the decision-making process. Third, the decision-making process of Millennial moms is dissimilar and unique from other service product decision-making processes. The study has provided comprehensive and valuable insights that will benefit policymakers, service providers, and marketers in understanding the consumer birthplace decision-making process. Further, the study's findings provided a roadmap that will assist service providers in effectively tailoring their maternity service product offerings.